Association between anxiety and severe quality-of-life impairment in postmenopausal women: Analysis of a multicenter Latin American cross-sectional study - Núñez Pizarro, Jorge L. (2017)
Objective: To evaluate associations between anxiety and severe impairment of quality of life (QoL) in Latin American postmenopausal women. Methods: This was a secondary analysis of a multicenter cross-sectional study among postmenopausal women aged 40 to 59 from 11 Latin American countries. We evaluated anxiety (The Goldberg Depression and Anxiety Scale), and QoL (Menopause Rating Scale [MRS]), and included sociodemographic, clinical, lifestyle, and anthropometric variables in the analysis. Poisson family generalized linear models with robust standard errors were used to estimate prevalence ratios (PRs) and 95% CIs. There were two adjusted models: a statistical model that included variables associated with the outcomes in bivariate analyses, and an epidemiologic model that included potentially confounding variables from literature review. Results: Data from 3,503 women were included; 61.9% had anxiety (Goldberg). Severe QoL impairment (total MRS score >=17) was present in 13.7% of women, as well as severe symptoms (MRS subscales): urogenital (25.5%), psychological (18.5%), and somatic (4.5%). Anxiety was independently associated with severe QoL impairment and severe symptoms in the epidemiological (MRS total score: PR 3.6, 95% CI, 2.6-5.0; somatic: 5.1, 95% CI, 2.6-10.1; psychological: 2.8, 95% CI, 2.2-3.6; and urogenital: 1.4, 95% CI, 1.2-1.6) and the statistical model (MRS total score: PR 3.5, 95% CI, 2.6-4.9; somatic: 5.0, 95% CI, 2.5-9.9; psychological: 2.9, 95% CI, 2.2-3.7; and urogenital: 1.4; 95% CI, 1.2-1.6). Conclusions: In this postmenopausal Latin American sample, anxiety was independently associated with severe QoL impairment. Hence, screening for anxiety in this population is important.